Assessing Reliability for Quantifying Social Interactions among Crayfish - Lee Ann Smith; Jeremy Nadolski; Grace Jacobs; Jodi M. Ogle; Madhusudan P. Srinivasan; Hannah N. Tanner; Elizabeth R. Steele; Nicole T. Marguerite; Sonya Bierbower; Slane Steen; Isaac Easterling; Abigail Greenhalgh; et al. (International Journal of Zoology)
Animal behavior is a useful way to evaluate the environment and can be a predictive tool to assess not only the effects of treatments in a laboratory setting, but also the status of ecological habitats. As invasive species of crayfish encroach on territories of native species, the social behaviors and interactions can be informative for ecological studies. For a wider and more impactful effect, training community scientists using a scoring system to record the social interactions of crayfish that includes both the level of aggression and intensity would provide useable data to monitor the environment. Amateur scientists with little training were fairly reliable in their average scoring of the crayfish and the maximum behavior score with an expert as well as among themselves. However, the number of interactions was not as a reliable metric to compare with the expert or just among the amateurs.